Desain dan Pengembangan Kurikulum dan Perencanaan PAK Keluarga dalam Menjadikan Keluarga sebagai Garam dan Terang - Liberto Ripan Petrus Hutagalung; Andar Gunawan Pasaribu (Pusat Riset dan Inovasi Nasional, 2025)
This article discusses the design and development of a Christian Religious Education (PAK) curriculum for families with the aim of making families salt and light in the world. Referring to the teachings of Jesus in the Gospel of Matthew 5:13-16, families are expected to be role models in everyday life through the application of Christian values. This curriculum includes teaching about family theology, the application of Christ's teachings in practical life, character building, and strengthening relationships between family members. The method used in this article is a qualitative method of data obtained through interviews with several families who have implemented the PAK Family curriculum. Curriculum planning is adjusted to the age and developmental stage of family members, and is accompanied by an evaluation to assess the effectiveness of implementation. The role of the church in supporting the implementation of this curriculum is also discussed, where the church functions as a partner in providing resources and training for families. This research is expected to provide a positive contribution to the formation of families based on the Christian faith, which can have a broad impact on society as true salt and light.